Measurements of Rayleigh–Brillouin scattering spectra of Ar, N2, and CH4 at pressures up to 20 atm - Teav, Ketana; Steinberg, Adam M. (Proceedings of the Combustion Institute, 2023)
This paper describes the spectral measurement of Rayleigh–Brillouin scattering (RBS) in Ar, N2, and CH4 at 300 K and pressures up to 20 atm, which is relevant for the application of filtered Rayleigh scattering (FRS) diagnostics at elevated pressure. The measurement scheme for RBS spectra was relatively novel, based on an air-spaced virtually imaged phased array (VIPA), capable of rapid acquisition at high resolution. However, the VIPA’s nonuniform dispersion, irregular instrument response function, and sensitivity to local ambient conditions challenged the reconstruction of high-fidelity lineshapes in frequency space. Nonuniform dispersion was addressed using the VIPA dispersion function, and sensitivity of the air-spaced optic to the refractive index of air was minimized by tracking local temperature and pressure during measurements. Irregular instrument response was remedied with a computational model of the VIPA’s optical field, and by deconvolution. A comparison of experimental lineshapes with model predictions by Tenti S6 yielded good agreement. In the kinetic and nominal transition regimes, local residuals were within 3% for Ar and N2, and 5–10% for CH4. Beyond the transition regime, experimental lineshapes continued to display good qualitative agreement, with frequency shifts of the Brillouin peaks representing the main deviation from model prediction. Artifacts in the experimental data from uncertainty and the deconvolution algorithm were identified and discussed. This work establishes an experimental foundation for future measurements of RBS spectra, which will assist in the development of FRS diagnostics of reacting flows at high pressure.